Relational Database for Health Care - Wanra Tarigan; Rafika Sari Br Sembiring (Postgraduate, University of Mataram, 2023)
The development of activities within a company will increase the complexity of business processes with transactional data that will increase from time to time. This is also experienced in health services, which are health service institutions for the community and certainly involve a lot of data in their operations. Starting from the registration process, medical/paramedical examinations, hospitalization, purchasing drugs, laboratories, etc. These data certainly require a container that can be used to manage the data needed in the transaction. So that later these data can be easily integrated and processed into a useful output. Database as one of the media that can be used to accommodate all supporting data. By using a database, and the features of a Database Management System (DBMS) can help companies carry out their operations more effectively and efficiently. The research method used refers to the analysis and design. In the method of analysis, literature studies are carried out from various supporting sources and observations of samples of research objects. While the design method refers to database design using the Database Lifecycle approach